The Extent of Settling down Check Disputes through Arbitration in Jordanian (International Journal of Scientific Research and Management (IJSRM), 2018)
The check is a tool of fulfillment in the commercial law. The legislator has been subject to strict penalties. The check includes two parts, civil part and criminal part. In this research, we discussed the possibility of resorting to arbitration in settling down check disputes. As a result, the criminal case falls or ends between the parties to the dispute after they agree to resolve the dispute between them except for a public right that cannot be waived. But in the same time no public rights exists it civil disputes, in the time that criminal protection for check in Jordan is coming as extra protection to the check because many reasons which the spread use of check as a credit tool is the most important. The purpose of this research is to demonstrate the extent to which arbitration can be applied as a mean of settling down disputes in checks disputes, which are considered as commercial papers and to determine the extent to which this affects the criminal case. This section has been dealt with in two parts: Section One, the possibility of arbitration in check disputes. In the second section, the effects of resorting to commercial arbitration, and we concluded that there is a possibility to resort to arbitration in checks disputes regarding the two forms of disputes that may be initiates, especially when we know that the Jordanian legislator was silent regarding this issue. Accordingly, it is recommended that specific legal provisions relates to arbitration be issued clarifying the possibility of using arbitration in check disputes because of its positive aspects in commercial disputes.